The Use of Exogenous Lung Surfactant (Poractant Alfa) in Acute Respiratory Failure by Drowning - Mario Pezzi; Francesco Givigliano; Ottorino Perrone; Annamaria Scozzafava; Pietro Maglio; Patrizia Casella; Anna Maria Giglio; Mario Verre; Carlo Pietro Voci (Case Reports in Critical Care)
Drowning is an acute respiratory failure as a result from immersion or submersion of the airways in a liquid medium (predominantly water). Inhalation of water causes severe lung damage due to the destruction of pulmonary surfactant, resulting in decreased lung elasticity, alveolar collapse, alteration of ventilation-perfusion ratio, intrapulmonary blood shunting, hypoxia, acute lung injury, and Acute Respiratory Distress Syndrome (ARDS). Poractant alfa (Curosurf®), a natural surfactant effective in the treatment of newborn respiratory distress, has been used in various forms of ARDS, but in drowning syndromes, experience is still poor. We describe a series of nine clinical cases of drowning, six adults and three children, treated in our Intensive Care Unit (ICU) with endobronchial administration of poractant alfa. After 24 and 48 hours of administration in all cases, there was an improvement in arterial blood gas analysis (ABG) parameters and imaging. All patients were discharged without clinical consequences.